PENGUKURAN INDIKATOR PROGRAM PEMBANGUNAN BIDANG SOSIAL KOTA MALANG TAHUN 2022 - Ucca Arawindha; Atu Bagus Wiguna; Zakaria (PANGRIPTA, 2023)
Abstract: Measurement of Social Development Indicators for the City of Malang is carried out to be able to measure the achievement of social sector program performance indicators in 2021 and 2022 until the second quarter, review the targets of social development indicators that have been set, present social indicator data, and be able to provide recommendations policies and steps that need to be taken by the City Government of Malang based on the results of the study. There are 23 (twenty three) P-RPJMD programs and 54 (fifty four) indicators in the social sector that are in accordance with the related regional apparatus. Measuring indicators of the social development program has analysis techniques for measuring the achievements of indicators in the social sector, measuring the effectiveness of target achievements, classifying the level of effectiveness of target achievements, and identifying the determinants of program implementation. The results of the analysis show that 80% of the indicators have a very high level of effectiveness in 2021. This effectiveness has increased from the previous year by a difference of 23%. However, there are still 3 (three) indicators that have a very low level of effectiveness and 2 (two) indicators that have a low level of effectiveness.